Education and Economic Growth in Morocco: what’s new through Vector AutoRegressif (VAR) approach? - Yahya Fikri; Mohamed Rhalma; Husni Muhamad Rifqi (Yayasan Ghalih Pelopor Pendidikan, 2025)
The purpose of this article is to investigate This study examines the connection between Morocco's economic growth (EG) and education from 1990 to 2023 using a Vector AutoRegressif (VAR) approach. The primary inquiry is whether education and economic growth (EG) are related in the short and long term. The World Bank provided the data, which includes significant attributes like economic growth (EG) and education. The goal of this research is to increase understanding of Morocco's development factors by illuminating the relationship between economic growth and education. It also aims to improve the conversation about the effectiveness of fiscal policy considering socioeconomic shifts. As a result, we can formulate the following issue: What connection exists, in the Moroccan context, between economic growth and education? In conclusion, each nation, like Morocco, may offer unique and inspiring solutions to the problems of the modern world, which call for a careful but daring approach. Morocco is a prime example of how to strike a balance between tradition and progress while actively engaging in the most important debates of our time, balancing cultural heritage and innovation, local concerns and global perspectives.